Television watching time and cognitive development in young children - Anak Agung Ayu Windi Antari; I Gusti Ayu Trisna Windiani; Djauhar Ismail (Indonesian Pediatric Society Publishing House, 2012)
Background Television viewing for children is prevalent. There have been few Indonesian studies on the association between duration of television watching and cognitive development in young children. Objective To assess cognitive development in young children who watched < 1 hour, 1-2 hours, or > 2 hours of television daily. Methods We conducted a cross-sectional study at 6 prekindergartens in Denpasar, Bah. We included 135 subjects in this study. Cognitive development was measured by the Mullen Scales ofEarly Learning (MSEL). Data was analyzed by one-way analysis of variance (ANOVA) test, post-hoc test, and univariate analysis of covariance (ANCOVA) with significance level of P < 0.05. Results There were significant differences among composite standard score in children who watched television < 1 hour, 1-2 hours, and> 2 hours per day (P=0.035). The mean composite standard score in children who watched television 1-2 hours daily was 6.087 points higher than in those who watched television < 1 hour daily (P=0.013, 95%CI 1.29 to 10.88) and 4.213 points higher than in those who watched television > 2 hours daily (P=0.045, 95%CI 1.08 to 8.51). There was an association between television watching time and cognitive development (P=0.001). Conclusion Television watching time was statistically associated with cognitive development in young children, where those viewing television 1-2 hours daily scoring significantly higher than those viewing < 1 hour and > 2 hours daily. [Paediatr lndones. 2012;52:32-7].